Manejo dos resíduos da colheita de Pinus taeda L. e sua relação com compactação do solo, exportação de nutrientes e potencial energético - Szymczak, Denise Andréia (2015)
Economic development and environmental issues have increased the demand for alternative energy sources, particularly renewable, highlighting the use of forest residual biomass as an energy input. However, the removal of residue lights up the question on the implications for soil physical quality and nutritional sustainability of the site. Therefore, this study aimed to establish a quantitative standard of residual biomass that can be removed from the plot without the physico-chemical properties of the soil from being compromised in the matters of sustainability. It attempted to also know the heat capacity of this residues for use with energy production purposes. For this, was held a study in Quedas do Iguaçu – PR, in a stand of Pinus taeda L. of 25 years from Araupel S.A. The soil of the area was classified as Dystroferric Red Oxisol. We carried out the forest inventory, and collecting the pine biomass for the quantification of nutrients above the ground, in order to determine the amount of residue which was produced by forest harvesting. The experimental design was randomized blocks in split plot, with four replications. They composed the treatments, different proportions of crop residue on the soil (0%, 25%, 50%, 75% and 100%) and on these the harvester and forwarder traffic, simulating cutting and loading timber. The occasion of the collection of soil samples before and after the traffic, was the subplot. The results indicated that the amount of residues generated in timber harvesting was 75.8 Mg ha-1, composed by 67.3 Mg ha-1 of branches, needles and tree top of pine and 8.5 Mg ha-1 of biomass of understorey. The pine residues represent 18.2% of total biomass of pine trees. The traffic of machines of forest harvesting conducted on different proportions of this residues, generated in the compression topsoil (0 a 10 cm) regardless of the quantity of residues disposed on the ground, without reaching levels considered critical for the development of the root system of pine. The amount of residue which can be withdrawn from the plot is 50% and has favorable heat-transfer characteristics for use in energy production, since it is conducted to the recovery of nutrients removed and thus maintain the sustainability of the site.